The Effect of Organizational Commitment , Organizational Communication and Organizational Culture on Employee Performance: Pengaruh Komitmen Organisasi, Komunikasi Organisasi, dan Budaya Organisasi Terhadap Kinerja Karyawan - Syaifuddin, Muhammad; Sumartik, Sumartik (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of organizational commitment, organizational communication and organizational culture on employee performance (Study at Lazismu Umsida). This research is a type of quantitative research with hypothesis testing. The sample used in this study were 40 Lazismu Umsida employees. The analytical tool used in this study is multiple linear regression analysis using SPSS Version 22 for windows. The primary data in this study were obtained from a questionnaire whose measurement was using a Likert scale which was tested for validity and reliability. The results of this study prove that organizational commitment affects employee performance, organizational communication affects employee performance, organizational culture also affects employee performance. In addition, Organizational Commitment, Organizational Communication and Organizational Culture have a simultaneous effect on Employee Performance.